E-learning Self-Perceived Readiness Among Dental Students: A Multi-Institution Study (Medical Forum Monthly, 2024)
Objective: This study aimed to evaluate dental students' perceived readiness for e-learning in low and middle-income countries, employing the Online Learning Readiness Scale (OLRS).Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the College of Dentistry, King Faisal University Al- Ahsa, Saudi Arabia, from March and August 2023.Methods: An electronic survey was conducted among dental students in six countries: Egypt, India, Nigeria, Pakistan, Saudi Arabia, and Sudan. Convenience and snowball sampling techniques were employed to recruit the participants and disseminate the survey links through collaborative networks.Results: This study included 665 dental students; 59.4% were female and 73.4% were younger students. Most participants (74%) were enrolled in public institutions, with 54.4% categorized as senior students. The highest average score for the agreement was 52.9% in online communication self-efficacy. Saudi Arabia scored highest across all constructs, while Sudan recorded the lowest, primarily due to insufficient institutional support. Notably, computer/internet self-efficacy demonstrated significant correlations with all other constructs, while the motivation for learning correlated significantly with self-directed learning and online communication self-efficacy.Conclusion: The findings underscored the importance of assessing dental students' perceived readiness for e-learning, which emerges as a crucial factor in ensuring the efficacy of educational processes. While overall readiness was evident among dental students, variations were observed across demographic factors such as age, gender, study level, and institutional type. The disparity in readiness levels highlights the necessity for tailored approaches to support e-learning initiatives, particularly in regions with limited institutional resources.